Food insecurity as a risk factor for preterm birth: a prospective facility-based cohort study in rural Haiti - Richterman, Aaron (BMJ Glob Health, 2020)
INTRODUCTION: Haiti has an estimated neonatal mortality rate of 32/1000 live births, the highest in the Western Hemisphere. Preterm birth and being born small for gestational age (SGA) are major causes of adverse neonatal outcomes worldwide. To reduce preterm birth and infants born SGA, it is important to understand which women are most at risk and how risk varies within countries. There are few studies estimating the prevalence and risk factors for these conditions in Haiti, particularly in rural regions. METHODS: We conducted a prospective cohort study of pregnant women at a rural tertiary care centre in Haiti from May to December 2017. We collected data during interviews and from the medical record. We built multivariable models to identify risk factors for preterm birth and being born SGA among women who had a facility-based delivery. RESULTS: 1089 pregnant women delivered at the hospital and were included in this analysis. Median gestational age at delivery was 38 weeks (IQR 36–40). In multivariable analyses, risk factors for preterm birth included maternal age <20 years (adjusted OR (AOR) 1.76, 95% CI 1.14 to 2.72) and >34 years (AOR 1.46, 95% CI 1.01 to 2.11) and severe hunger in the household (AOR 1.57, 95% CI 1.09 to 2.26). Risk factors for SGA were age >34 years (AOR 1.76, 95% CI 1.18 to 2.59), twin pregnancy (AOR 3.28, 95% CI 1.20 to 8.95) and first pregnancy (AOR 1.57, 95% CI 1.12 to 2.23). Number of prior abortions was associated with reduced risk for SGA (AOR 0.41, 95% CI 0.17 to 0.97). CONCLUSIONS: Food insecurity as a risk factor for preterm birth stands out as an important addition to the understanding of the risk of neonatal morbidity and mortality. This association highlights a potentially important intervention target to improve birth outcomes and suggests that food support has an important role to play for pregnant women who are food insecure in low-income settings.